Utilization of waste cathode ray tube funnel glass for ultra-high performance concrete. (10th March 2020) - Liu, Tiejun; Wei, Huinan; Zou, Dujian; Zhou, Ao; Jian, Hongshu
Abstract: Cathode ray tube (CRT) funnel glass is classified as a hazardous waste because it contains lead, which can endanger the environment and human health. In this paper, an innovative cementitious material, ultra-high performance concrete (UHPC) was introduced to recycle hazardous waste CRT without lead extraction. Crushed CRT funnel glass without lead extraction was used to replace sand as fine aggregate in various ratios in UHPC. The mechanical properties and toxic heavy metal leachability of UHPC were investigated. Results showed that the addition of CRT glass can increase the flowability and decrease the compressive and flexural strength of UHPC. Analyses by X-ray diffraction and scanning electron microscopy demonstrated that the CRT glass increases the porosity, inhibits cement hydration, and weakens the interfacial transition zone, resulting in the reduced strength of UHPC. Meanwhile, the leached lead concentration of UHPC was still below regulatory limit of U.S. code even when the replacement ratio reaches 100%. The working principle behind the sharp drop in leached lead in UHPC was proposed, that is the dense microstructure and low permeability coefficient of UHPC can effectively restrain the lead leaching from CRT glass. The findings of this study can provide an effective alternative to recycling hazardous waste CRT without limitations on the replacement ratio and safety concern. Graphical abstract: Image 1 Highlights: Recycling of waste CRT funnel glass without lead treatment through UHPC is explored. The influence of waste CRT funnel glass on the properties of UHPC is investigated. UHPC with waste CRT funnel glass fulfills safety requirement from US code. Lead leaching is inhibited in UHPC and its working principle has been revealed.